The Evaluation of Different Treatments of Incipient Caries Lesions: An in Situ Study of Progression Using Fluorescence-based Methods - Diniz, M.; Campos, P.; Souza, M. [UNESP]; Guare, R.; Cardoso, C.; Lussi, A.; Bresciani, E. [UNESP] (Operative Dentistry Inc, 2021)
This study aimed to evaluate in situ the inhibition of incipient caries lesion progression using different treatment protocols and to evaluate the effectiveness of fluorescence-based methods (DIAGNOdent, DIAGNOdent pen, and VistaProof fluorescence camera [FC]) in monitoring this process. The research was conducted in four phases: (1) at baseline, (2) after a first cariogenic challenge, (3) after treatment modalities, and (4) after a second cariogenic challenge. Sixteen volunteers used intraoral acrylic palatal appliances, each containing six enamel blocks (n=96). The cariogenic challenge was performed using a 20% sucrose solution over a 14-day period. The appliances were removed eight times a day and, upon removal, two drops of the solution were placed onto each enamel block. The enamel blocks were randomly assigned to three treatment groups: fluoride varnish ([FV] Duraphat; n=32), resin infiltrant ([RI] Icon; n=32), and adhesive system ([AS] Scotchbond; n=32). At the end of each phase, the surface microhardness (SMH) was measured, and two trained examiners evaluated the specimens using fluorescence-based methods. In addition, integrated mineral loss (Delta Delta Z; vol%.min x mu m) and lesion depth (Delta LD; mu m) were evaluated using transverse microradiography. A two-way analysis of variance and a Tukey post hoc test were calculated (alpha=5%). Significant differences in SMH were observed according to the treatment, phases, and interaction of factors (p<0.001). Treatment with FV resulted in significantly higher SMH values in phases 3 and 4 compared to RI and AS, with the last two treatments resulting in similar values (p>0.05). The Delta Delta Z value was similar for FV and AS but significantly higher for RI (p=0.016). Delta LD was not significantly different among the groups (p=0.126). Significant differences in the measurement of fluorescence for each fluorescence-based method were observed between each phase of the study (p<0.05). It can be concluded that all treatments were effective in inhibiting the in situ progression of incipient lesions, although to different degrees, with minor mineral loss changes observed for the AS and FV. Besides, all fluorescence-based methods tested, except for that using the FC device, were effective in monitoring caries lesion progression.